THE IMPACT OF MASS MEDIA TOOLS ON EFL STUDENTS' SPEAKING SKILLS - Muhsin Omay Yanar; Prof. Dr. BirsenTütüniş (Informascope, 2016)
It is a well-known fact that mass media tools have tremendous impact on people all around the world, and it is also becoming a significantly important research area for scholars, educators and researchers in applied linguistics. EFL students in Turkish context complain about their speaking skills in English despite their exposure to English for a long period of primary and secondary education. Knowing this fact as a member of this community, an exploratory practice was conducted as a detailed study to find out young adult EFL students' (38) perceptions on the impact of mass media tools in the improvement of their speaking skills. The results displayed the fact that subject EFL students believed in the positive effect of mass media tools on their speaking skills but they were not aware of.